Effect of Eight Weeks of Sensorimotor Training on Knee Proprioception and Balance in Elderly Women: A Randomized Controlled Clinical Trial - Nasim Shahravan; Sajad Roshani; Afshin Moghadasi (Shiraz University of Medical Sciences, 2023)
Background: A common issue experienced by the elderly, often due to specific diseases or the natural aging process, is a decline in balance and posture control. This study aimed to investigate the impact of an eight-week sensorimotor training program on the balance and proprioception of older women. Methods: This study was a randomized controlled clinical trial conducted with the participation of older women aged 60-75 who frequented gyms in Urmia. From this population, thirty older women were randomly selected, meeting specific inclusion criteria, and were purposively divided into two groups: the experimental group (with an average age of 70.06±2.64 years, height of 156.13±6.14 cm, and weight of 73.11±7.81 kg) and the control group (with an average age of 67.93±2.12 years, height of 154.15±7.22 cm, and weight of 70.83±5.22 kg). The experimental group underwent an 8-week sensorimotor training program, consisting of three sessions per week, while the control group did not receive any training. Knee proprioception was assessed before and after the training by capturing photographs at a flexion angle of 40-60 degrees while standing. Additionally, static and dynamic balance was evaluated using the Sharpened Romberg Test and Time of Up and Go Test, respectively. The collected data were analyzed using ANCOVA, and the significance level was set at P≤0.05. Results: After the training intervention, the experimental group exhibited a noteworthy decrease in the absolute error of angle reconstruction (P=0.001). Moreover, there was a substantial enhancement in both static balance, with eyes open and closed (P=0.001), and dynamic balance (P=0.001) compared to the control group. Conclusion: the results of this study suggest that sensorimotor training can effectively enhance proprioception and improve balance in elderly individuals. This improvement is attributed to the positive impact of sensorimotor training, particularly in closed-chain movements, which strengthens the proprioceptive feedback from the muscles of the lower limbs. Consequently, this contributes to better balance and proprioception in older adults.